Green House and Ḥalāl Budget Allocation for Sustainable Household Finance Realization: Green House dan Halal Allocation Budget untuk Perwujudan Keuangan Rumah Tangga Berkelanjutan - Nikmatul Masruroh; Ahmad Fadli; Attori Alfi Shahrin; Yazidul Fawaid (El-Qist: Journal of Islamic Economics and Business (JIEB), 2023)
This research aims first to describe household budget allocation and the realization of sustainable financial management in the household, both formulations of the greenhouse model and ḥalāl allocation budget in realizing sustainable finance for households in Indonesia. The research method used is a library study approach with secondary data sources. Data was obtained from BPS, OJK and observations in villages where the community allocated a budget for greenhouses and environmental health. The collected data was analyzed using Ibn Khaldūn's thoughts on Trade and Social Change. The results of this research are as follows: first, budget allocation considers the sources of income they have; households tabulate their needs and make a percentage budget allocation. In this budget allocation, not everything is used for consumption but also for savings and righteous charity activities. The realization of sustainable financial management is carried out using the greenhouse model and ḥalāl budget allocation. Greenhouses are realized by the community participating in waste banks, Sustainable Food House Areas or Climate Resilient Integrated Service Post (Postaklim). Through this, community economic empowerment occurs. Second, the greenhouse model collaborates with the ḥalāl budget allocation model so that there is no waste in household expenditure because sustainable finances in the household do not only talk about current financial existence but also financial existence in the future.